Polyamide material and preparation method thereof
By using modified thermal conductivity masterbatches, including polyamine materials, thermal fillers and dispersants in nylon materials, and fully mixing them through high-temperature grinding, the problem of taking into account both thermal conductivity and toughness of nylon materials is solved, and the improvement of high thermal conductivity and low-temperature toughness is achieved.
Patent Information
- Application Number
- CN202510003112.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The poor thermal conductivity of existing nylon materials limits its application in some areas with high requirements for thermal conductivity. At the same time, the toughness of the material is also low, making it difficult to meet the low temperature demand.
Modified thermal conductivity masterbatches, including polyamine materials, thermal fillers and dispersants, are fully mixed by high-temperature grinding to improve the dispersion of thermal fillers and the toughness of the material.
It effectively improves the thermal conductivity of polyamide materials, and improves the low-temperature toughness of the materials, solving the problem of taking into account both thermal conductivity and toughness.
Smart Images

Figure BDA0005226020590000021 
Figure BDA0005226020590000061 
Figure BDA0005226020590000062
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer material synthesis and processing, and specifically relates to a polyamide material and a preparation method thereof. Background Art
[0002] As a commonly used engineering plastic, nylon material has the advantages of good mechanical properties and chemical corrosion resistance. It is widely used in many fields such as transportation, construction, aerospace, home, and industry. However, its thermal conductivity is poor, which is also a major pain point of all polymer materials. Therefore, it limits its application in some fields with high requirements for thermal conductivity.
[0003] At present, the main method to improve the thermal conductivity of nylon materials is to add thermally conductive fillers, but traditional thermally conductive fillers have problems such as poor dispersibility and poor compatibility with the nylon matrix, which affect the performance of the material. Patent CN112029275A discloses a thermally conductive nylon material, which improves the dispersibility of the thermally conductive filler by introducing glass fiber and coupling agent, thereby improving the thermal conductivity of the product. However, the toughness of the material itself is low, which has great limitations in the relevant low-temperature demand field. CN115572477B discloses a high thermal conductivity nylon composite material, which uses graphite and fiber thermally conductive fillers of different sizes, dissolves the coupling agent in water, dilutes it with ethanol, and then pours it on the thermally conductive filler to improve the compatibility of the material and improve the thermal conductivity of the material. This method has limited improvement in the toughness of the material. Patent CN102408710A discloses an epoxy-modified graphite and thermally conductive nylon composite material and a preparation method thereof, wherein the surface of graphite is modified by using an epoxy-type bifunctional epoxy compound, wherein one epoxy group undergoes a physical and chemical reaction with the graphite surface, so that reactive epoxy groups are grafted onto the graphite surface, thereby greatly improving the thermal conductivity of the nylon material to above 2.3W / mK. However, the epoxy functional groups are too active, which will cause a significant increase in the viscosity of the material.
[0004] In view of this, with regard to the existing technical solutions, on the one hand, it is necessary to improve the thermal conductivity problem of existing materials, and on the other hand, it is necessary to take into account the high toughness of the material itself. Therefore, it is urgent to develop a high thermal conductivity and low temperature resistant polyamide material and a preparation method thereof. Summary of the invention
[0005] The invention provides a polyamide material and a preparation method thereof. The heat-conductive filler of the invention can be effectively dispersed to improve the thermal conductivity of the material, and its chain extension effect can improve the toughness of the material.
[0006] In order to achieve the above invention object, the technical solution adopted by the present invention is as follows:
[0007] A polyamide material comprising the following components in mass fractions:
[0008] Polyamide 37~79wt%
[0009] Modified thermal conductive masterbatch 20~60wt%
[0010] Optional additives 0-3 wt%.
[0011] Preferably, the polyamide is an aliphatic polyamide containing a -CO-NH- structure, wherein the ratio of the number of methylene groups to the number of amide groups is greater than 6.0, and comprises one or more of PA6, PA66, PA610, PA612, PA1012, PA11, PA12, PA1212, PA614, PA616, and PA618, and the ratio of the terminal carboxyl group concentration to the terminal amino group concentration, eq-COOH / eq-NH2, is 1 to 20, preferably 3 to 15.
[0012] Preferably, the modified thermally conductive masterbatch comprises a polyamine material, a thermally conductive filler and a dispersant.
[0013] Preferably, the polyamine material includes one or more of diamine, triamine, tetramine, polyimide, etc. More preferably, the structural formula of the polyamine material is as follows:
[0014]
[0015] The R1, R2, R3, and R4 are the same or different and are independently selected from H, a C1-C16 alkyl or aryl group, wherein the alkyl or aryl group includes a straight-chain alkyl group, a branched alkyl group, a cycloalkyl group, an alkyl-substituted aryl group, or an amino-substituted alkyl or aryl group, and one or more carbon atoms on the alkyl group may be substituted by a nitrogen atom.
[0016] The R is a C1-C16 alkylene or arylene group, and the alkylene or arylene group includes a straight-chain alkylene group, a branched alkylene group, a cycloalkyl group, an alkyl-substituted aryl group, or an amino-substituted alkyl or aryl group, and one or more carbon atoms on the alkyl group may be substituted by a nitrogen atom.
[0017] Preferably, the number average molecular weight of the polyamine material is less than 20,000, and the melting point is ≤ 295°C. A relatively large molecular weight is not conducive to the dispersion of the thermally conductive filler in the composition. Although it improves the low-temperature toughness of the material to a certain extent, it hinders the dispersion of the thermally conductive filler and reduces its thermal conductivity. The present invention uses a relatively low molecular weight material to achieve the dispersion of the thermally conductive filler and reduce the interface gap between the filler and the polyamide material, thereby improving the material performance.
[0018] The dispersant can be selected from one or more of silane coupling agent, titanate coupling agent, aluminate coupling agent, zirconate coupling agent, etc., which contains corresponding ester bonds, carboxyl groups, etc., and can achieve lubrication when the thermal conductive filler is premixed, which helps to fully mix the thermal conductive filler with the polyamine material.
[0019] The polyamine material can be liquid or solid.
[0020] The thermally conductive filler of the present invention is selected from any one or more of aluminum oxide, graphite, zinc oxide, magnesium oxide, boron nitride, zinc nitride, aluminum nitride, magnesium hydroxide, aluminum hydroxide, and silicon carbide, preferably aluminum oxide or graphite.
[0021] Preferably, the preparation method of the modified thermally conductive masterbatch is: a polyamine material, a thermally conductive filler and a dispersant are mixed and ground to obtain the modified thermally conductive masterbatch.
[0022] Preferably, the grinding temperature is 60°C to 120°C, and more preferably 80°C to 100°C.
[0023] The present invention pre-treats the heat-conducting filler and grinds it at high temperature. Sufficient grinding is conducive to sufficient mixing of the polyamine material and the heat-conducting filler, making the material more conducive to subsequent extrusion processing. The grinding temperature is preferably 80-100°C.
[0024] The grinding equipment described in the present invention can be a ball mill, a planetary grinder, a vibration grinder, etc. according to the working principle, or a mixer that helps solid / liquid dispersion or solid and solid dispersion. Low-speed, high-speed and other equipment can also be selected according to different speeds.
[0025] The mass ratio of the heat-conductive filler, the polyamine material and the dispersant added in the present invention is 50-98:1-20:1-10, preferably 70-95:3-15:1-5.
[0026] The present invention limits the end group ratio of the polymer material, modifies the surface of the inorganic filler, and preferably reacts with the polyamine substance that reacts with the end group, which is beneficial to improving the material performance.
[0027] The additive components of the present invention include one or more of antioxidants, light stabilizers, lubricants, flame retardants, pigments, leveling agents, chain extenders, thermal conductors, conductive additives and other thermoplastics.
[0028] The light stabilizer described in the present invention includes an ultraviolet absorber and a light stabilizer. The ultraviolet absorber mainly includes one or more of benzoic acid, benzophenone derivatives, benzotriazole, etc. The light stabilizer mainly includes a hindered amine stabilizer. The two can be compounded and used in a weight ratio of 0.5 to 2:1. Suitable ones include but are not limited to UV770, UV944, UV312, etc.
[0029] The lubricant described in the present invention is one or more of calcium stearate, polyethylene wax and ethylene distearamide.
[0030] The antioxidant of the present invention includes antioxidants used alone or in combination. As a specific embodiment, the antioxidant may include one or more of hindered amines, hindered phenol / semi-hindered phenol antioxidants, phosphites, phosphites, inorganic or organic cuprous iodide (CuI), potassium iodide (KI), etc. Suitable examples include but are not limited to 1098, 168, H10, H3336, H3386, etc.
[0031] The present invention also provides a method for preparing the polyamide material, which comprises mixing polyamide, modified thermal conductive masterbatch and optional additives and then extruding and granulating the mixture through an extruder to obtain the polyamide material of the present invention.
[0032] Preferably, the extruder is a twin-screw extruder, and the screw length-diameter ratio of the twin-screw extruder is 35 to 44:1, which can be 35:1, 36:1, 38:1, 40:1, 42:1, 44:1, etc.
[0033] The extrusion temperature is 240-280°C, for example, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C or 280°C, etc.
[0034] In view of the above, compared with the prior art, the present invention has several advantages:
[0035] The use of a relatively weakly reactive modified group has a mild reaction, and a polyamine material with a small molecular weight is used to modify the thermal conductive filler to improve the thermal conductivity of the polymer material itself. Due to its mild reactivity, the viscosity of the material itself is prevented from being excessively increased, and the toughness of the material itself is greatly improved. The modified thermal conductive masterbatch of the present invention is conducive to dispersion in the system and reduces its interface boundary. It not only plays a compatibility role and assists dispersion, but also plays a synergistic toughening role due to the filling of the thermal conductive agent itself, thereby improving the overall impact resistance of the material. DETAILED DESCRIPTION
[0036] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0037] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0038] Main raw material sources
[0039] Table 1 Source of raw materials
[0040] Raw material grade Material Type supplier Wanamid L3000 Polyamide Wanhua Chemical Group Co., Ltd. Alumina Thermally conductive fillers Shandong Lier New Materials Co., Ltd. graphite Thermally conductive fillers Aladdin Reagent Polyethyleneimine Polyamine materials Aladdin Reagent Triethylenetetramine Polyamine materials Aladdin Reagent Silane coupling agent Dispersants Guangzhou Aikopu New Materials Titanate coupling agent Dispersants Guangzhou Aikopu New Materials N493 Toughening agent DOW Chemistry Antioxidant 1098 Antioxidants BASF SE Antioxidant 168 Antioxidants BASF SE Black mother Masterbatch Cabot Corporation UV312 Light Stabilizer BASF SE
[0041] Main test methods
[0042] 1. Tensile test:
[0043] The tensile properties of polyamide compositions were tested according to ISO 527 1A specimens.
[0044] 2. Impact test:
[0045] The tensile properties of polyamide compositions were tested according to ISO 179 1eA specimens.
[0046] 3. Thermal conductivity test
[0047] The tensile properties of polyamide compositions are tested according to the ISO22007 transient plane heat source method.
[0048] Example
[0049] Preparation of modified thermal conductive masterbatch The polyamine material, thermal conductive filler and dispersant used to prepare the thermal conductive masterbatch are weighed according to the proportions in Table 2.
[0050] Add it into the grinding equipment and grind it at 80℃ for 5 minutes to obtain the modified thermal conductive masterbatch.
[0051] Table 2 Mass ratio of modified thermal conductive masterbatch
[0052]
[0053] Preparation of polyamide composition
[0054] Examples and Comparative Examples
[0055] Add the raw materials according to the proportions in Table 3, mix them for 2 minutes using a high-speed mixer at a speed of 700 rpm, put them into a twin-screw extruder, and undergo traction, cooling, cutting, and granulation.
[0056] Table 3 Polyamide composition component ratio (wt%)
[0057]
[0058]
[0059] The polyamide composition embodiments and comparative examples were tested and verified by the above test method, and the specific performance is shown in Table 4.
[0060] Table 4 Performance of Examples and Comparative Examples
[0061]
[0062] By comparing the examples with the comparative examples, the scheme of the present invention can effectively improve the thermal conductivity of the polyamide material, and the method can effectively improve the low-temperature toughness of the material.
[0063] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A polyamide material, characterized in that: The following components are included in the mass fraction: Polyamide 37~79wt% Modified thermal conductive masterbatch 20~60wt% Optional additives 0-3 wt%.
2. The polyamide material according to claim 1, characterized in that: The polyamide is an aliphatic polyamide containing a -CO-NH- structure, wherein the ratio of the number of methylene groups to the number of amide groups is greater than 6.0, and includes one or more of PA6, PA66, PA610, PA612, PA1012, PA11, PA12, PA1212, PA614, PA616, and PA618; Preferably, the ratio of the terminal carboxyl concentration to the terminal amino concentration of the polyamide (eq-COOH / eq-NH2) is 1 to 20, preferably 3 to 15.
3. The polyamide material according to claim 1 or 2, characterized in that: The modified thermally conductive masterbatch comprises a polyamine material, a thermally conductive filler and a dispersant.
4. The polyamide material according to any one of claims 1 to 3, characterized in that: The polyamine material includes one or more of diamine, triamine, tetramine, and polyimide. More preferably, the structural formula of the polyamine material is as follows: R1, R2, R3, and R4 are the same or different and are independently selected from H, C1-C16 alkyl or aryl groups, wherein the alkyl or aryl groups include straight-chain or branched alkyl groups, cycloalkyl groups, alkyl-substituted aryl groups, or amino-substituted alkyl or aryl groups, and one or more carbon atoms on the alkyl group may be substituted by a nitrogen atom; R is a C1-C16 alkylene or arylene group, wherein the alkylene or arylene group includes a straight-chain alkylene group, a branched-chain alkylene group, a cycloalkyl group, an alkyl-substituted aryl group, or an amino-substituted alkyl or aryl group, and one or more carbon atoms on the alkyl group may be substituted by a nitrogen atom; Preferably, the number average molecular weight of the polyamine material is less than 20,000 and the melting point is ≤ 295°C; Preferably, the dispersant is selected from one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and a zirconate coupling agent; Preferably, the thermally conductive filler is selected from any one or more of alumina, graphite, zinc oxide, magnesium oxide, boron nitride, zinc nitride, aluminum nitride, magnesium hydroxide, aluminum hydroxide, and silicon carbide, preferably alumina or graphite.
5. The polyamide material according to any one of claims 1 to 4, characterized in that: The preparation method of the modified thermal conductive masterbatch is as follows: a polyamine material, a thermal conductive filler and a dispersant are mixed and ground to obtain the modified thermal conductive masterbatch; Preferably, the grinding temperature is 60°C to 120°C, and more preferably 80°C to 100°C.
6. The polyamide material according to any one of claims 1 to 5, characterized in that: First, the thermal conductive filler is pretreated and ground at 80-100°C; Preferably, the mass ratio of the thermal conductive filler, the polyamine material and the dispersant added is 50-98:1-20:1-10, preferably 70-95:3-15:1-5.
7. The polyamide material according to any one of claims 1 to 6, characterized in that: The additive components include one or more of antioxidants, light stabilizers, lubricants, flame retardants, pigments, leveling agents, chain extenders, thermal conductors, conductive additives and other thermoplastics.
8. The polyamide material according to claim 7, characterized in that: The light stabilizer includes an ultraviolet absorber and a light stabilizer, the ultraviolet absorber includes one or more of benzoic acid, benzophenone derivatives, benzotriazole, etc., and the light stabilizer includes a hindered amine stabilizer. The two can be compounded and used in a weight ratio of 0.5 to 2:1, including but not limited to UV770, UV944, and UV312; Preferably, the lubricant is one or more of calcium stearate, polyethylene wax, and ethylene distearamide; Preferably, the antioxidant comprises an antioxidant used alone or in combination. As a specific embodiment, the antioxidant may include one or more of hindered amines, hindered phenol / semi-hindered phenol antioxidants, phosphites, phosphites, inorganic or organic cuprous iodide, potassium iodide, including but not limited to 1098, 168, H10, H3336, H3386.
9. The method for preparing a polyamide material according to any one of claims 1 to 8, characterized in that: The polyamide, the modified thermal conductive masterbatch and the optional additives are mixed and then extruded and granulated by an extruder to obtain the polyamide material.
10. The preparation method according to claim 9, characterized in that: The extruder is a twin-screw extruder, and the screw length-to-diameter ratio of the twin-screw extruder is 35-44:1; And / or, the extrusion temperature is 240-280°C.
Citation Information
Patent Citations
Nylon 66 composite material with high heat conductivity and preparation method thereof
CN102408710A
Heat-conducting nylon material as well as preparation method and application thereof
CN112029275A
A high thermal conductivity nylon composite material and preparation method thereof
CN115572477B